Effects of COVID-19 on Regional and Gender Equality in Sub-Saharan Africa : Evidence from Nigeria and Ethiopia - Aoyagi, Chie. (Washington, D.C. : International Monetary Fund, 2021)
The labor structure in sub-Saharan Africa is characterized by a high share of informal employment in the rural agricultural sector. The impact of COVID-19 on female employment may not appear to be large as the share of such employment is particularly high among women. Nevertheless, widespread income reduction was observed both in rural and urban households. This could worsen the opportunities for women as husbands' control over the household resource is the norm. The paper also finds that rural children struggled to continue learning during school closures. Gender-sensitive policies are needed to narrow the gap during and post-pandemic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economics Of Gender; Education; Labor Discrimination; Particular Labor Markets; Urban, Rural, and Regional Economics